University School Involvement and Educational Transformation. Another Teacher Education for Another School. - Leite-Méndez, Analía Elizabeth; Rivas-Flores, José Ignacio; Fernández-Torres, Pablo; Márquez-García, María Jesús; Cortés-González, Pablo; González-Calvo, Gustavo (My University, 2023)
Teacher training in Spain suffers from a technocratic approach that segregates theory and practice, in a hierarchical relationship. It assumes that it is necessary to have a previous theoretical framework in order to apply it in teaching practice. Students must take a minimum of 1 or 2 years of theoretical content, before doing internships in a school. These internships, in turn, are structured and respond to the academic demands of the University's teaching staff. In this way, future teachers live an artificial experience of what the teaching profession is. Thus raised, it becomes very difficult for there to be a change in the narrative of the profession that allows them to adopt a transforming role of the school. Rather, they are forced to reproduce practices, traditions and strategies lived in his transit through the school as a student, as has already been widely documented in the literature (Rivas, et al., 2015, 2017, 2020; Zeichner, 2010; Jagla, et al., 2013; Hargreaves y O´Connor, 2020; De Sousa Santos, 2007; González y Arias, 2017; Bhabha, 1990). The teacher education proposal that we have been developing for more than 15 years, in the subjects in which we teach, tries to subvert this epistemological order, through a school-university collaboration project. The aim is to create a new training space in which both institutions collaborate in a joint education proposal, in which each one contributes a dimension: a space for experience and a space for reflection. The objective is to blur the boundaries between theory and practice that allows students to build a professional perspective more committed to change and educational transformation. The students spend part of their course time collaborating with relevant educational projects in a school and alternatively attend classes at the university to rebuild their experience in these schools through a process of collaborative reflection (Leite et al., 2018; Márquez, et al., 2020, 2022; Fernández, et.al.,2019 )
Keywords: Profesores - Formación profesional; Teacher training; Collaboration; Educational community; Third space